Human Resource Management and Politics and Public Administration in India - gogoi, Lenin (International Journal of Scientific Research and Management (IJSRM), 2015)
India stands for democracy that has established a parliamentary form of political system for fulfilling the interests of the people. In a democracy, people can be regarded as the ultimate source of power generation and authorities of the rulers are conferred by the people. Similarly power is related with politics and public administration. In other words, politics is struggle for power and public administration is related with the execution of power. However it is very difficult to determine the achievements of India as a democracy towards uplifting democratic values and national objectives. Here, one of the major democratic values to the mainstream is human resource management in India. It is closely related with development process and growth of the country. This paper has been made to understand the relationship between human resource management and politics and public administration in the light of existing literatures and evidences.